Play in hospitals : real life perspectives - Everett, Nicky; Hubbuck, Catherine; Brown, Fraser, 1951- (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2023)
"Exploring how practitioners make use of play's developmental benefits and therapeutic healing properties to aid the child's health care journey, this reflective book expands and enhances the knowledge base underlying the practice of play in hospitals. Drawing on the collective work of over 30 play specialists, child life specialists, play service managers, lecturers and researchers, this book is unique in all it offers to paediatric practitioners and settings, in training and in practice. It is an important resource for healthcare play specialists, playworkers, children's nurses, occupational therapists and more"--
Keywords: Play therapy; Children -- Hospital care; MEDICAL / Allied Health Services / General; MEDICAL / Nursing / Pediatric & Neonatal; MEDICAL / Allied Health Services / Occupational Therapy